EFFECTS OF ROSIN SIZING AGENT ON THE DIMENSIONAL STABILITY OF Styrax tonkinensis WOOD - Thi Thanh Hien, Nguyen; Van Chu, Tran (Journal of Forestry Science and Technology, 2018)
Wood protection efficacy of boron compounds against biological agents, ﬂame retardancy, and suitability to the environment is well known. Nevertheless, they have limited utility in outdoor applications due to their high solubility in water which cause leaching from impregnated wood. Rosin is a product obtained from pines and some other plants. It is abundant, natural, and renewable. Over the years, rosin has been widely used in the paper industry as a sizing agent. Moreover, rosin sizing agent was also demonstrated to have a certain effect on the fixation of boron in wood. Therefore, the aim of this study was to evaluate the effect of rosin upon dimentional stability of styrax wood treated with mixtures of 3% boric acid and 1.0%, 2.0%, or 4.0% rosin sizing agent. The results indicated that all rosin-boron treatments decreased the moisture absorption, water absorption and swelling properties of wood, whilst increasing water repellent efficiency and anti-swelling efficiency to approximately 30% after 30-day immersion in water. This result showed that the use of rosin alone or combination with boron to impregnate styrax wood could reduce swelling of wood due to water/moisture absorption during use and contribute to increased dimensional stability of wood.